Role of Alphacalcidol to Reduce Pain and Serum Cartilage Oligomeric Matrix Protein in Elderly with Knee Osteoarthritis - Zaki, Achmad; Prihartono, Nurhayati Adnan; Ronoatmodjo, Sudarto; Djuwita, Ratna; Prasetyo, Sabarinah; TuaLubis, Andri Maruli; Rimbawan, Rimbawan; Rahim, Agus Hadian (Bangladesh Journal of Medical Science, 2022)
Objective : To determine the effect of Alphacalcidol supplementation on pain based on WOMAC pain index and joint cartilage condition based on cartilage oligomeric matrix protein (COMP) serum markers in knee osteoarthritis (OA) elderly patients. Materials andMethods : This is a randomized, double-blind, and placebo-controlled trial. Symptomatic knee OA elderly subjects visited our clinic in Jakarta July-December 2017 were recruited. History taking, physical examinations, and knee radiology were performed. Serum Vitamin D (25(OH)D) and COMP were analysed using chemiluminescent immunoassay and enzyme-linked immunosorbent assay, respectively. Body mass index, physical activity, sun exposure frequency, and dietary vitamin D were assessed. Subjects were randomly allocated to either intervention group to be given 1 μg Alphacalcidol or control group to be given placebo for 12 weeks. Comparation analysis of WOMAC pain index and serum COMP concentration between both groups was performed. Results : There were 146 subjects participated this study. Increases of 25(OH)D were found in intervention group (2.63 ±11.24 nmol/L, p=0.05) and control groups (1.09±9.42 nmol/L, p=0.28). Alphacalcidol significantly reduced pain based on WOMAC indicator with mean reduction differences of intervention group compared to control group was 2.174±1.060 (p=0.00). COMP serum level was reduced with mean reduction differences of intervention group compared to control group was 38.15±87.553 ng/ ml (p=0.39). Alphacalcidol and gender were the determinants of WOMAC pain index reduction (p=0.00 and p=0.06, respectively) while Alphacalcidol was the only serum COMP level change determinant (p=0.39). Conclusions :Alphacalcidol administration reduced pain based on WOMAC indicator and COMP serum in knee OA elderly subjects. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 759-771